RANCANG BANGUN MODEL PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) MENGGUNAKAN PADDLE BREAST WHEEL - Nur, Ichlas; Rais, Wahmin; Effiandi, Nota; Zamri, Aidil; Yetri, Yuli (Jurnal Rekayasa Mesin, 2024)
The need for electrical energy is increasing along with technological advances. In addition to the large population in an area, the variable economic activity of the population, which continues to increase to meet their daily needs, also has an impact on increasing the need for electrical energy. Demand for electrical energy is in line with increased economic activity. Therefore, developing renewable energy to provide sufficient electricity supply is very important. In this research, the modeling of a Micro Hydro Power Plant (PLTMH) has been designed using a breast wheel with a semicircular blade shape, a wheel diameter of 20cm, and 10 blades. The wheel model has 5 variations of water level (head) calculated from the water level in the reservoir to the water level in the wheel with 3 variations of ball valve openings. It was observed that the highest efficiency is at a head height of 0.8 m with a pipe cross-sectional area (A) of 0.0002 m2 with an efficiency of 70.11 percent. The increase in the flow rate of water flowing towards the breast wheel turns out to cause the wheel rotation to decrease. The decrease in the wheel's rotation is related to the increase in turbulence (collision) due to the large discharge of water against the wheels' walls. It can be concluded that the combination of gravity and water propulsion can move the breast wheel so that it produces electrical energy.